Nigerian music: Returning the favour of cultural imperialism? - Aruku, Kalita Joseph; Ikankang, Joseph; Egere, Nicholas; Utsu, Charlse Ushie (Journal of Language, Literature, Social and Cultural Studies, 2025)
This article explores the intricate dynamics of cultural imperialism as it pertains to the Nigerian music scene, which has become increasingly prominent on the global stage. Initially dominated by Western influences, Nigeria's musical landscape faces a transformative moment, characterized by the emergence of Afrobeat, Afropop, and other indigenous genres that blend traditional sounds with contemporary styles. Using a mixed qualitative research method that included case study, ethnography, content analysis and documents analysis we analyzed the ways in which Nigerian artists are harnessing global platforms to assert their cultural identity while simultaneously reclaiming narratives that may have been overshadowed by foreign dominance. Through examining case studies of prominent musicians and their international collaborations, we highlight Nigeria's role in reshaping global music trends and question whether this phenomenon represents a form of cultural return, a transactional exchange, or a new type of cultural imperialism in reverse. By engaging with theories of globalization, cultural exchange, and identity formation, this article seeks to contribute to the discourse on cultural power dynamics and the impact of Nigerian music on both local and global scales, ultimately posing the question: Is Nigeria returning the favor of cultural imperialism, or is it redefining the terms of engagement?